2023
DOI: 10.1093/jrr/rrad048
|View full text |Cite
|
Sign up to set email alerts
|

Assessing target localization accuracy across different soft-tissue matching protocols using end-exhalation breath-hold cone-beam computed tomography in patients with pancreatic cancer

Abstract: The purpose of this study was to retrospectively assess target localization accuracy across different soft-tissue matching protocols using cone-beam computed tomography (CBCT) in a large sample of patients with pancreatic cancer and to estimate the optimal margin size for each protocol. Fifty-four consecutive patients with pancreatic cancer who underwent 15-fraction volumetric modulated arc therapy under the end-exhalation breath-hold condition were enrolled. Two soft-tissue matching protocols were used accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This study also observed inter-observer variability, consistent with findings from previous studies. 3,8,9,[17][18][19] These findings emphasize the need for auto-matching techniques to minimize inter-observer variability and achieve consistent soft-tissue matching.…”
Section: Inter-observer Variabilitymentioning
confidence: 78%
See 2 more Smart Citations
“…This study also observed inter-observer variability, consistent with findings from previous studies. 3,8,9,[17][18][19] These findings emphasize the need for auto-matching techniques to minimize inter-observer variability and achieve consistent soft-tissue matching.…”
Section: Inter-observer Variabilitymentioning
confidence: 78%
“…3 Sasaki et al demonstrated substantial interobserver variability and increased time requirements for soft-tissue matching in pancreatic cancer, particularly among trainees with limited experience in IGRT. 8 Furthermore, Zhang et al conducted an analysis of the impact of inter-observer variability, underscoring its greater influence on organs at risk (OARs) than on the target in prostate cancer. 9 Current radiotherapy systems are unable to overcome the well-acknowledged challenges associated with softtissue matching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation